Phenotypic and functional alteration of CD45+ immune cells in the decidua of preeclampsia patients analyzed by mass cytometry (CyTOF) - Fu, Min; Zhang, Xiaowei; Liu, Chunfeng; Lyu, Jinli; Liu, Xinyang; Zhong, Shilin; Liang, Yiheng; Liu, Ping; Huang, Liting; Xiao, Zhansong; Wang, Xinxin; Liang, Xiaoling; et al. (Frontiers in Immunology, 2023)
Preeclampsia (PE) is a severe placenta-related pregnancy disease that has been associated with maternal systemic inflammation and immune system disorders. However, the distribution and functional changes in immune cells of the maternal-placental interface have not been well characterized. Herein, cytometry by time-of-flight mass spectrometry (CyTOF) was used to investigate the immune atlas at the decidua, which was obtained from 4 PE patients and 4 healthy controls. Six superclusters were identified, namely, T cells, B cells, NK cells, monocytes, granulocytes and others. B cells were significantly decreased in the PE group, among which the reduction in CD27+CD38+ Breg-like cells may stimulate immune activation in PE. The significantly increased migration of B cells could be linked to the significantly overexpressed chemokine C-X-C receptor 5 (CXCR5) in the PE group, which may result in the production of excessive autoantibodies and the pathogenesis of PE. A subset of T cells, CD11c+CD8+ T cells, was significantly decreased in PE and might lead to sustained immune activation in PE patients. NK cells were ultimately separated into four subsets. The significant reduction in a novel subset of NK cells (CD56-CD49a-CD38+) in PE might have led to the failure to suppress inflammation at the maternal-fetal interface during PE progression. Moreover, the expression levels of functional markers were significantly altered in the PE group, which also inferred that shifts in the decidual immune state contributed to the development of PE and might serve as potential treatment targets. This is a worthy attempt to elaborate the differences in the phenotype and function of CD45+ immune cells in the decidua between PE and healthy pregnancies by CyTOF, which contributes to understand the pathogenesis of PE, and the altered cell subsets and markers may inspire the immune modulatory therapy for PE.